2015
DOI: 10.1016/j.atmosenv.2015.08.039
|View full text |Cite
|
Sign up to set email alerts
|

Impact of wildfires on size-resolved aerosol composition at a coastal California site

Abstract: Species other than K are more reliable biomass burning tracers in region. Sulfate and nitrate peak concentrations shift to larger sizes in wildfire periods. Chloride depletion due to high levels of acidic species during wildfire periods. Soil species levels (e.g., Si, Fe, V) were enhanced during wildfires. CCN composition is dominated by ammonium during wildfire periods. Size-resolved aerosol composition measurements were conducted at a coastal site in central California during the Nucleation in California Exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
103
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 89 publications
(115 citation statements)
references
References 45 publications
12
103
0
Order By: Relevance
“…Together with the appreciable amount of P and K, this results in the higher particle diversity seen in this cluster. Further supporting this cluster's identity is that enhancement of these elements have been observed previously during biomass burning events in the presence of a background rich in marine aerosols [64,65]. [61,62].…”
Section: Soot Clusters (Lds1 Lds2 Hds)supporting
confidence: 60%
“…Together with the appreciable amount of P and K, this results in the higher particle diversity seen in this cluster. Further supporting this cluster's identity is that enhancement of these elements have been observed previously during biomass burning events in the presence of a background rich in marine aerosols [64,65]. [61,62].…”
Section: Soot Clusters (Lds1 Lds2 Hds)supporting
confidence: 60%
“…The cloudy side organic mass concentration at wheels-in and FT altitudes was greater than any other concentrations observed in the three flights. showed that continental air masses often influence layers above the stratocumulus cloud deck in the study region even though the bulk low-level flow is alongshore; during this flight, biomass-burning plumes were being advected and mixed into the study region from near the OregonCalifornia border (Maudlin et al 2015) that are likely linked to the enhanced organic levels observed.…”
Section: ) Aerosol Spatial Profilesmentioning
confidence: 99%
“…4). With regard to emissions sources that could promote nucleation in the study region, major ones include shipping (e.g., SO 2 ; Coggon et al, 2012), marine biogenic emissions (e.g., dimethylsulfide, amines; Sorooshian et al, 2009Sorooshian et al, , 2015Youn et al, 2015), and continental emissions (e.g., NH 3 , volatile organic compounds; Maudlin et al, 2015;Braun et al, 2017). The combination of cool and moist air, high actinic solar fluxes, relatively low SA concentrations as compared to other studies with nucleation events (e.g., Alam et al, 2003;Cai et al, 2017), and several precursor vapor sources builds a case for why nucleation resulted in the highest number concentration of particles with D p between 3 and 10 nm in the EIL relative to other vertical layers.…”
Section: Nucleation In the Eilmentioning
confidence: 99%